최척전｣에 나타난 가족 서사의 특징 - 김영미(Kim, Youngmi) (열린정신 인문학 연구, 20(3), 2019)
「최척전」은 남원의 최척 가족이 전쟁을 만나 각각 중국, 일본, 베트남등지를 떠돌다가 결국 모든 가족이 우여곡절 끝에 고향 남원으로 돌아와만나게 되는 이야기이다. 가족의 이산(離散)과 만남을 다루고 있는 소설로, 서사적으로는 ‘가족 복원’의 구조적 특징을 보인다. 그런데 「최척전」은 ‘가족 복원의 서사’ 속에 또 다른 축의 서사 전략을 담고 있다. 그것은 바로옥영 중심의 열녀 서사이다. 소설의 제목만 봐서는 최척이 서사의 주인공이 될 것 같지만 실제로 「최척전」의 모든 이야기 전개는 ‘옥영 중심’으로진행된다. 「최척전」은 ‘옥영을 위한, 옥영의 서사’라고 할만하다. 그리고 이 두 축인 가족 서사와 옥영의 서사가 자연스럽게 교착될 수 있는 지점은 바로 옥영의 정절이다. 옥영의 정절을 통해 가족 ‘복원’의 서사와 옥영의 ‘열녀’ 서사가 이루어진 것이다. 전쟁이라는 외부 충격을 극복하고 국제적으로 이산했던 가족들이 다시만나 온전한 가족을 이루기 위해서, 즉 완전한 가족 복원의 서사를 위해옥영의 정절은 무엇보다 중요한 전제 조건이 된다. 가족의 완전한 복원은가족들이 다 모이기만 한다고 해서 가능한 것이 아니다. 옥영이 정조를 잃고 단순히 살아 돌아와 ‘환향녀’라고 손가락질을 받는다면 가족은 온전히복원될 수 없기 때문이다. 그래서 옥영은 정절 보존을 위해 남장을 해야 했고 그토록 빈번하게 자결을 시도할 수밖에 없었다. 결국 옥영은 정절을 지킨 ‘귀향녀’가 되어 헤어졌던 가족들이 다 함께 모여 행복해질 수 있는 가족 서사를 완성할 수있었다. 이러한 열녀 담론은 「최척전」처럼 일관되지는 않지만 어우야담‘홍도 이야기’에서도 일정 부분 드러난다. 본 연구는 「최척전」이 표면적으로 가족 복원의 서사 속에 또 하나의 열녀 서사를 내재하고 있음을 밝혔다. 「최척전」에 나타난 교착적 서사 구조를 이해함으로써 표면 서사 구조 속에 감춰진 열(烈)의 이데올로기를 파악할 수 있다는 연구 의의를 갖는다. Choicheokjeon is about Choi-cheok whose family suffer from a war, roaming around China, Japan, Vietnam, etc, returning to Namwon, his hometown after many twists and turns and meet together. This has the structure of “family restoration”, which reveals in the novel of family scattering and meeting again. But this hides another narrative strategy in the “narrative of family restoration”. It is Okyoung-centered narrative. Judging from the title, Choi-cheok is likely to be a protagonist but all the story goes on with Okyoung. Therefore, this novel is the narrative ‘for Okyoung, and of Okyoung’. Also the two narratives, that is Choi-cheok’s family one and Okyoung’s one, naturally adhere the her chastity. This is because family restoration narrative and a chaste woman’s narrative are accomplished through her chastity. Okyoung’s chastity is the most important premise for Choi-cheok’s scattered family to overcome the outer impact of a war, to meet again and to make a complete family, that is, the family restoration narrative. Being family members together doesn’t means the whole family restoration. If Okyoung survives and returns home after losing chastity and being pointed at with scorn as a “whore”, the family can’t be said to be fully restored. So she disguised herself as a man and tried to kill herself frequently. The chaste woman narrative of Okyoung’s story is seen in the “Hongdo’s story” in the Eouyadam. As a result, she becomes a woman who returns home with chastity and completes a family narrative in which family come together and stay happy. This study examines that Choicheokjeon has a chaste woman narrative in the surface of the family restoration narrative. It is meaningful to understand the ideology of chastity in the adhered narrative in the Choishekjeon. KCI Citation Count: 0